2010
DOI: 10.1007/s10295-010-0911-6
|View full text |Cite
|
Sign up to set email alerts
|

Heterotrophic nitrification–aerobic denitrification by novel isolated bacteria

Abstract: Three novel strains capable of heterotrophic nitrification-aerobic denitrification were isolated from the landfill leachate treatment system. Based on their phenotypic and phylogenetic characteristics, the isolates were identified as Agrobacterium sp. LAD9, Achromobacter sp. GAD3 and Comamonas sp. GAD4, respectively. Batch tests were carried out to evaluate the growth and the ammonia removal patterns. The maximum growth rates as determined from the growth curve were 0.286, 0.228, and 0.433 h(-1) for LAD9, GAD3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(57 citation statements)
references
References 31 publications
2
54
0
1
Order By: Relevance
“…A comparison with the literature confirms that the performance of the Azospira sp. OGA 24 are in line (sometimes better) of the most common bacteria employed in the biological treatment of polluted waters [7,12,23,[27][28][29]. …”
Section: Resultsmentioning
confidence: 99%
“…A comparison with the literature confirms that the performance of the Azospira sp. OGA 24 are in line (sometimes better) of the most common bacteria employed in the biological treatment of polluted waters [7,12,23,[27][28][29]. …”
Section: Resultsmentioning
confidence: 99%
“…isolated from the soil [42]. Further investigations are necessary to evaluate if heterotrophic nitrification [43] could be one of the well-known metabolisms of R. capsulatus.…”
Section: Batch Experiments On Mixed Liquor From Municipal Wastewater mentioning
confidence: 99%
“…With the increase of C/N in inflow, the AOB and nitrite oxidizing bacteria (NOB) significantly decrease, while the heterotrophic bacteria gradually increase [20,21]. In recent years, there are many reports about heterotrophic nitrification and aerobic denitrification [22][23][24]. Different from autotrophic nitrifiers, heterotrophicnitrifying bacteria can simultaneously using carbon and nitrogen pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in a high carbon and nitrogen wastewater treatment, a strong aeration is generally necessary, which might cause high dissolved oxygen (DO) concentration in the particles. And researches [22,23] showed that denitrification could be carried out in the presence of oxygen.…”
Section: Introductionmentioning
confidence: 99%